Biomarkers in the Diagnosis and Prognosis of Sarcoidosis: Current Use and Future Prospects - Kraaijvanger, Raisa; Janssen Bonás, Montse; Vorselaars, Adriane D. M.; Veltkamp, Marcel (Frontiers in Immunology, 2020)
Sarcoidosis is a heterogeneous disease in terms of presentation, duration, and severity. Due to this heterogeneity, it is difficult to align treatment decisions. Biomarkers have proved to be useful for the diagnosis and prognosis of many diseases, and over the years, many biomarkers have been proposed to facilitate diagnosis, prognosis, and treatment decisions. Unfortunately, the ideal biomarker for sarcoidosis has not yet been discovered. The most commonly used biomarkers are serum and bronchoalveolar lavage biomarkers, but these lack the necessary specificity and sensitivity. In sarcoidosis, therefore, a combination of these biomarkers is often used to establish a proper diagnosis or detect possible progression. Other potential biomarkers include imaging tools and cell signaling pathways. Fluor-18-deoxyglucose positron emission tomography and high-resolution computed tomography have been proven to be more sensitive for the diagnosis and prognosis of both pulmonary and cardiac sarcoidosis than the serum biomarkers ACE and sIL-2R. There is an upcoming role for exploration of signaling pathways in sarcoidosis pathogenesis. The JAK/STAT and mTOR pathways in particular have been investigated because of their role in granuloma formation. The activation of these signaling pathways also proved to be a specific biomarker for the prognosis of sarcoidosis. Furthermore, both imaging and cell signaling biomarkers also enable patients who might benefit from a particular type of treatment to be distinguished from those who will not. In conclusion, the diagnostic and prognostic path of sarcoidosis involves many different types of existing and new biomarker. Research addressing biomarkers and disease pathology is ongoing in order to find the ideal sensitive and specific biomarker for this disease.